CHARACTERS OF WAYANG GOLEK REOG PONOROGO IN PATRIOTISM EDUCATION LEARNING TO EARLY CHILDHOOD - Sulton .; Betty Yulia Wulansari; Prihma Sinta Utami (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2019)
This study aimed to get to know the characters of Wayang Golek Reog Ponorogo (Rod Puppet) in the learning of patriotism education to children in early childhood. This research used qualitative description research. The results of this study are the understanding of the characters of patriotism in the following characters: Prabu Klono Sewandono including wise, brave, and concerned with the interests of the people than personal interests. Patih Bujang Ganong has the characters of patriotism such as loyal and responsible.Warok has the character of patriotism like faithful, calm, and wise. Jathilan warriors are brave in defending the homeland, Singo Barong is loyal in defending the homeland.